Signet Ring Cell Carcinoma of the Lung: A Diagnostic Pitfall in Pregnancy - Sabine Danzinger; Wolfgang J. Köstler; Martin Funovics; Merima Herac; Leonhard Müllauer; Helmut Prosch; Heinz Kölbl (Hindawi Limited, 2019)
Lung cancer during pregnancy represents a rare disease. In this case report, we present a patient at advanced and metastasized stage of signet ring cell carcinoma who presented in the 22nd week of gestation.